A CLINICAL COMPARATIVE STUDY TO EVALUATE THE EFFECTIVENESS OF RASNA SWADAMSTRADI KSHEERAPAKA WITH SUKUMARAM KASHAYAM IN SPASMODIC DYSMENORRHOEA - Anisha A; Shahina Mole.S (International Journal of Ayurveda and Pharma Research, 2021)
Many women are familiar with the experience of spasmodic dysmenorrhoea, one of the commonest gynaecological conditions that affects the quality of life of many in their reproductive years. This condition manifested as painful menstruation, is the most frequently encountered gynaecological complaint and it can be included under Udavartha yonivyapat, caused by Apana vata vaigunya described in Ayurvedic classics. As the condition has significant effect on quality of life, personal health, and working hours and there are several limitations and adverse effects in modern medicine, its Ayurvedic management is of great importance. Randomized clinical study was conducted in Govt. Ayurveda College Hospital for Women and Children, Poojappura to evaluate the effectiveness of Rasna swadamstraadi ksheerapaaka in spasmodic dysmenorrhoea and to compare its result with that of Sukumaram kashayam. Total 30 patients between the age group 15-35 yrs were taken in to the study who had complaints of severe or moderate lower abdominal pain and associated complaints such as low back ache, nausea, vomiting, diarrhoea, and allocated them into two groups. Study group were treated with Rasna swadamstraadi ksheerapaaka and control group with Sukumaram kashayam. Administration of drug started10 days before menstruation and continued till 4th day of menstruation for 3 consecutive cycles for study group and control group. Follow up without medicine was done for next 3 consecutive cycles for both the groups. Results were analyzed and compared statistically. The research drug Rasna swadamstraadi ksheerapaaka had shown effectiveness in controlling pain in spasmodic dysmenorrhoea and associated symptoms like low back ache and nausea, but in the case of vomiting, and diarrhoea it showed less sustained action in follow up period. The control drug Sukumaram kashayam had also shown effectiveness in controlling pain in spasmodic dysmenorrhoea and associated complaints nausea and low back ache. But in the case of vomiting, and diarrhoea this medicine also showed less sustained action in follow up period. On conclusion the study revealed that the research drug Rasna swadamstraadi ksheerapaaka and control drug Sukumaram kashayam are equally effective in treating spasmodic dysmenorrhoea, without any side effects.